Exploration of Mango Fruits (Mangifera indica) as α-Glucosidase Inhibitors - Nadia Prilliane Putri; Khalida Shabiba Nursyamsi; Yanico Hadi Prayogo; Dina Ragillia Sari; Eka Budiarti; Irmanida Batubara (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Mango fruit (Mangifera indica L.) is the tropical fruit that grows easily in Indonesia with plenty varieties. This study aimed to determine the varieties of mango fruit and the most potent part of mango as antidiabetic agent through α-glucosidase inhibitory activities. Four types of mango fruit (indramayu, manalagi, harum manis, and budiraja) were used in this study. Each part of the mango fruit:peel, flesh, endosperm, and endocarp were extracted by maceration process with three different solvents (n-hexane, ethyl acetate (EtOAc), and ethanol (EtOH)). An ability of all 46 extracts in inhibiting the α-glucosidase at a concentration of 500 ppm were determined. Then 11 extracts with the high inhibition value were determined their IC50 (concentration to inhibit 50% activity) values. EtOAc extract of manalagi, indramayu, and budi raja endosperm had the lowest IC50 value which was not statistically significantly different (at 95%) with EtOAc extract of budi raja peel. The bioautographic Thin Layer Chromatogram showed that the most active band is characterized by white luminescence under UV 366 nm, yellow color under UV 254 and visible light. The band with Rf 0.93 from EtOAc endosperm extract of indramayu and manalagi and Rf 0.73 from EtOAc budi raja peel extract are the most active band which predicted as a flavonoid. The result adds the value of the peel and seed of mango, as well as an alternative in blood sugar control, which is easy to obtain, relatively cheap, and liked by the community.